Delaying factors for maternal health service utilization in eastern Ethiopia: A qualitative exploratory study. Issue 3 (May 2020) - Tesfaye, Gezahegn; Chojenta, Catherine; Smith, Roger; Loxton, Deborah
Abstract: Background: In Ethiopia, maternal health service utilization is still unacceptably low. The societal and cultural factors that constrain women from attending these services have not yet been sufficiently explored. Using qualitative methods, we aimed to explore the factors that delay maternal health service utilization in eastern Ethiopia. Method: A total of 13 audio-recorded focus group discussions were conducted comprising 88 participants. We conducted separate group discussions with reproductive aged women, mothers-in-law, traditional birth attendants, husbands, and Health Extension Workers to capture their knowledge, practices, feelings, thoughts and attitudes towards maternal health service utilization. The recorded sessions were transcribed into the local language and then translated into English for analysis. Result: The study identified a number of factors that may delay maternal health service utilization. Factors were grouped using the Three Delays model as a framework. Low level of awareness regarding need, poor involvement of husband, perceived absence of health problems, social power, community misperceptions and cultural restrictions, negative attitudes towards male midwives, acceptance of traditional birth attendants and poor social networking were Delay One factors. Lack of physical accessibility and high transportation costs were categorised as Delay Two factors for skilled birth care attendance. Perceived or experienced poor quality of care were categorised as Delay Three factors for both skilled birth and postnatal care utilization. Conclusion: Despite the ongoing government measures to improve maternal health service utilization in Ethiopia, numerous factors continue to contribute to delays in service use, which in turn contribute to high maternal mortality.